Effects of topdressing ratio and frequency on the dry matter, yield, and quality of tomato and celery under a small amount of continuous subsurface drip irrigation - Huang, Lingmiao; Yang, Peiling; Cui, Haobo; Sun, Zhanghao; Ren, Shumei; Wang, Zhaocheng (International Journal of Agricultural and Biological Engineering, 2023)
Compared with conventional full irrigation, the existing water-saving irrigation method achieves the purpose of water saving by actively controlling soil moisture. High-frequency irrigation can make the ideal conditions for soil water movement and root absorption of water and nutrients. This research used a plot experiment in a greenhouse and set up different fertilization amounts and frequencies during the growth stage to study the effects of small-amount and continuous subsurface drip irrigation on the dry matter, yield, and quality of tomato and celery. The results showed that the frequency of topdressing had a great influence on the dry matter accumulation of tomatoes, and the amount of topdressing had little effect on the fresh weight of the upper part of a tomato plant. The application of high-frequency fertilizer increased the dry matter accumulation in the underground part of the tomato. Under the premise given amount of total fertilization, the growth rate and yield of tomatoes were positively correlated with the amount of topdressing. The optimum fertilization frequency was 1 time during the first fruit stage, 3 times for the second fruit stage, and 5 times for the third fruit stage, the yield during the fourth stage was increased with higher frequency, and the topdressing was started ahead of the fourth fruit stage when the diameter of fruit was 40 mm. The lower fertilization frequency during the early stage and higher fertilization frequency during the later stage can increase the yield of celery. The higher ratio of topdressing, the higher frequency during the early growth stage, and the lower frequency during the later stage can achieve the best quality of celery.Keywords: fertilization frequency, continuous subsurface drip irrigation, topdressing fertilizer, tomato, celery DOI: 10.25165/j.ijabe.20231603.7465Citation: Huang L M, Yang P L, Cui H B, Sun Z H, Ren S M, Wang Z C. Effects of topdressing ratio and frequency on the dry matter, yield and quality of tomato and celery under small amount continuous subsurface drip irrigation. Int J Agric & Biol Eng, 2023; 16(3): 273–284.